1999
DOI: 10.1046/j.1440-1754.1999.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of gonadoblastoma in female patients with Y chromosome abnormalities and dysgenetic gonads

Abstract: We report two female patients with gonadal dysgenesis and sex chromosome mosaicism involving the Y chromosome. Conventional karyotyping was supplemented with fluorescent in situ hybridisation techniques in order to confirm the presence of Y chromosomes. One patient is a phenotypic female with karyotype 45,X/46,X,idic(Y)(q11.2). She underwent a laparoscopic gonadectomy at which streak ovaries without evidence of gonadoblastoma were removed. The second patient presented as a virilised female with karyotype 45,X/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 11 publications
0
16
0
2
Order By: Relevance
“…22 Data in the literature revealed 10 cases where the tumor developed during childhood, five of them had a 45,X/ 46,XY mixed gonadal dysgenesis and the diagnosis was performed only in one case at 9 months old while the rest were diagnosed around 10 years of age. [10][11][12][13][14][15] The other five patients had a 46,XY gonadal dysgenesis, one of them, a 3-year-old girl had campomelic dysplasia, sex reversal and bilateral gonadoblastoma while in the other four a WT1 mutation was observed. 16,[23][24][25][26] The presence of a suppress tumor mutation in these individuals could participate in early tumor development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Data in the literature revealed 10 cases where the tumor developed during childhood, five of them had a 45,X/ 46,XY mixed gonadal dysgenesis and the diagnosis was performed only in one case at 9 months old while the rest were diagnosed around 10 years of age. [10][11][12][13][14][15] The other five patients had a 46,XY gonadal dysgenesis, one of them, a 3-year-old girl had campomelic dysplasia, sex reversal and bilateral gonadoblastoma while in the other four a WT1 mutation was observed. 16,[23][24][25][26] The presence of a suppress tumor mutation in these individuals could participate in early tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis in infants is rare; [10][11][12] however, several cases were diagnosed around 10 year of age. [13][14][15][16][17] The presence of gonadoblastoma in young patients and the potential risk for malignant transformation is the main reason for early diagnosis and treatment in some cases of intersex patients. In this paper, we present the histological and molecular findings of four patients with gonadal dysgenesis, who developed gonadoblastoma in the first 2 years of life and one case with bilateral dysgerminoma diagnosed at 15 years of age.…”
mentioning
confidence: 99%
“…Evidence of Y-chromosomal material in the female karyotype is associated with a raised incidence of gonadoblastoma [6, 7]. Muroya et al [8]reported a patient with gonadoblatoma and mixed germ cell tumor, in whom Y-chromosomal material was found in the gonadoblastoma but absent in the mixed germ cell tumor, as a consequence of Y-chromosomal loss from rapidly proliferating gonadal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is recommended that the gonads should be removed before hormone treatment (Gibbons et al 1999;Gravholt et al 2000;Mazzanti et al 2005;Pena-Alonso et al 2005;Brant et al 2006).…”
Section: Molecular Genetic Analysismentioning
confidence: 99%